IDENTIFIKASI FRAGMEN HV1 DNA MITOKONDRIA INDIVIDU DATARAN RENDAH DAN DATARAN TINGGI - Satiyarti, Rina Budi; Aminah, Siti; Rosahdi, Tina Dewi (Biosfer: Jurnal Tadris Biologi, 2017)
An individual adaptation towards the geographical altitude associated with genetic factors, one of the genetic materials of the most widely used to study the characteristic of individuals in the population is the mitochondrial DNA.Based on that condition, this research will deciding human Fragmen HVI mtDNA from Indramayu as lowland individual and Sukabumi as highland individual. The purpose of this research is to identify hair root and the epithelial cell of the mouth as a source DNA mitochondrial that can used for a amplification of human fragment DNA mitokondria template and to identify fragment territory HV1 mtDNA by using Polimerase Chain Reaction (PCR) technic and detecting the yield of PCR from lowland and highland individual. The steps include the lysis to do the sample of the hair root and the epithelial cell of the mouth, amplified HV1 fragment mtDNA to utilize Polimerase Chain Reaction (PCR) technique and the result of PCR with elektroforesis gel agarosa. This research has been successfully, hair root and the epithelial cell can do analyze DNA mitochondrial marked by the fragment measuring 0,4 kb in the area D-Loop mtDNA and it can easier amplification is hair root characterized by the presence of DNA bands in agarose gel electrophoresis.